2021
DOI: 10.3390/ijms22010463
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Hepatic Encephalopathy and Diabetic Encephalopathy: The Brain-Liver Axis

Abstract: Hepatic encephalopathy (HE) is one of the main consequences of liver disease and is observed in severe liver failure and cirrhosis. Recent studies have provided significant evidence that HE shows several neurological symptoms including depressive mood, cognitive dysfunction, impaired circadian rhythm, and attention deficits as well as motor disturbance. Liver disease is also a risk factor for the development of diabetes mellitus. Diabetic encephalopathy (DE) is characterized by cognitive dysfunction and motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 141 publications
(69 reference statements)
0
7
0
Order By: Relevance
“…However, previous studies have emphasized that the central role of metabolic changes was subsequent to hyperammonaemia, including an alteration in glutamate/glutamine metabolism, increased neurosteroids, and dysregulation in GABAergic neurotransmission. 53,54 Increased extracellular glutamate leads to a hyperactivation of the N-methyl D-aspartate (NMDA) type of glutamate receptor, which contributes to neurodegeneration and death due to mitochondrial dysfunction, overproduction of reactive oxygen species (ROS), and stimulation of calcium-dependent enzymes. 55,56 Administration of THY-30 and THY-60 or Vit E showed a marked decrease in the signs mentioned above compared with the TAA group (Tables 2 and 3).…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have emphasized that the central role of metabolic changes was subsequent to hyperammonaemia, including an alteration in glutamate/glutamine metabolism, increased neurosteroids, and dysregulation in GABAergic neurotransmission. 53,54 Increased extracellular glutamate leads to a hyperactivation of the N-methyl D-aspartate (NMDA) type of glutamate receptor, which contributes to neurodegeneration and death due to mitochondrial dysfunction, overproduction of reactive oxygen species (ROS), and stimulation of calcium-dependent enzymes. 55,56 Administration of THY-30 and THY-60 or Vit E showed a marked decrease in the signs mentioned above compared with the TAA group (Tables 2 and 3).…”
Section: Food and Function Papermentioning
confidence: 99%
“…Astrocytic swelling and brain edema induced by ammonia and accumulation of osmotic glutamine could be the outcome of the downregulation of the genes coding for cytoskeletal network components implicated in glial cell volume regulation. 53,60 GFAP, a key marker of mature astroglia, is a filament cytoskeleton protein responsible for astrocyte structural and mechanical stability. 5,61 In the present work, the HE group showed a significant reduction in GFAP protein expression in the cerebral cortex, hippocampus, and striatum (Fig.…”
Section: Food and Function Papermentioning
confidence: 99%
“…23 Third, the neurocognitive consequences of diabetes, including increased permeability of the blood brain barrier and neuroinflammation related to hyperglycemia, can act synergistically with similar changes seen in HE. 24 Obesity and Sarcopenia. Obesity contributes to the metabolic syndrome that is associated with NAFLD.…”
Section: Nafldmentioning
confidence: 99%
“…The presence of abnormal Alzheimer’s type II astrocytes is a major neuropathological characteristic feature of BDL-induced chronic HE ( 26 27 28 ). Numerous studies have shown that ammonia- induced synaptic defect and astrocytic dysfunction in chronic HE is implicated in the development of cognitive and motor alterations in chronic HE ( 28 29 30 31 32 33 ). In the current study, we observed the presence of Alzheimer’s type II astrocytosis in brain histology in BDL-induced rats.…”
Section: Discussionmentioning
confidence: 99%